Primary Care Physicians' Collection, Comfort, and Use of Race and Ethnicity in Clinical Practice in the United States - Vence L. Bonham; Nkeiruka I. Umeh; Nkeiruka I. Umeh; Brooke A. Cunningham; Khadijah E. Abdallah; Sherrill L. Sellers; Lisa A. Cooper (Mary Ann Liebert, 2017)
Purpose: The clinical utility of race and ethnicity has been debated. It is important to understand if and how race and ethnicity are communicated and collected in clinical settings. We investigated physicians' self-reported methods of collecting a patient's race and ethnicity in the clinical encounter, their comfort with collecting race and ethnicity, and associations with use of race in clinical decision-making. Methods: A national cross-sectional study of 787 clinically active general internists in the United States. Physicians' self-reported comfort with collecting patient race and ethnicity, their collection practices, and use of race in clinical care were assessed. Bivariate and multivariable regression analyses were conducted to examine associations between comfort, collection practices, and use of race. Results: Most physicians asked patients to self-report their race or ethnicity (26.5%) on an intake form or collected this information directly from patients (26.2%). Most physicians were comfortable collecting patient race and ethnicity (84.3%). Physicians who were more comfortable collecting patient race and ethnicity (?=1.65; [95% confidence interval; CI 0.03?3.28]) or who directly collected patients' race and ethnicity (?=1.24 [95% CI 0.07?2.41]) were more likely to use race in clinical decision-making than physicians who were uncomfortable. Conclusions: This study documents variation in physician comfort level and practice patterns regarding patient race and ethnicity data collection. As the U.S. population becomes more diverse, future work should examine how physicians speak about race and ethnicity with patients and their use of race and ethnicity data impact patient?physician relationships, clinical decision-making, and patient outcomes.